2007
DOI: 10.1186/bf03353102
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of the external field to the observatory annual means and a proposal for their corrections

Abstract: In this study we separate, interpret and explain magnetospheric and ionospheric signals present in the observatory annual means. The data from 46 European geomagnetic observatories collected over 42 years are used. To characterise the various field components, we use predictions from latest magnetic field models. The core field and its secular variation are described by the CM4 model, and the magnetospheric contributions are successfully removed by parameterising the POMME model with the Dst index. We regard … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 13 publications
(20 reference statements)
2
14
0
2
Order By: Relevance
“…We confirmed the well known presence in the annual means of geomagnetic elements of a 11-year solar-cyclerelated (SC) signal due to incomplete averaging out external effects and their induced counterparts, modulated by solar activity (Chapman and Bartels, 1940;Yukutake, 1965;Bhargava and Yacob, 1969;Alldredge, 1975Alldredge, , 1976Courtillot and Le Mouël, 1976;Alldredge et al, 1979;Yukutake and Cain, 1979;Demetrescu et al, 1988;Verbanac et al, 2007;Wardinski and Holme, 2011) and quantitatively showed that the time change of the signal is of the same order of magnitude as that of the internal ingredients of the measured field. As a consequence, the SC signal should be filtered out before any discussion on SV.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…We confirmed the well known presence in the annual means of geomagnetic elements of a 11-year solar-cyclerelated (SC) signal due to incomplete averaging out external effects and their induced counterparts, modulated by solar activity (Chapman and Bartels, 1940;Yukutake, 1965;Bhargava and Yacob, 1969;Alldredge, 1975Alldredge, , 1976Courtillot and Le Mouël, 1976;Alldredge et al, 1979;Yukutake and Cain, 1979;Demetrescu et al, 1988;Verbanac et al, 2007;Wardinski and Holme, 2011) and quantitatively showed that the time change of the signal is of the same order of magnitude as that of the internal ingredients of the measured field. As a consequence, the SC signal should be filtered out before any discussion on SV.…”
Section: Discussionsupporting
confidence: 67%
“…Alexandrescu et al, 1995), but, we think, with increased possibilities for external effects to leak into the models. The presence in annual mean data of a solar-cycle-related (SC) signal due to incomplete averaging out of external effects, modulated by the solar activity, has long been recognized (Chapman and Bartels, 1940;Yukutake, 1965;Bhargava and Yacob, 1969;Alldredge, 1975Alldredge, , 1976Courtillot and Le Mouël, 1976;Alldredge et al, 1979;Yukutake and Cain, 1979;Demetrescu et al, 1988;Verbanac et al, 2007;Wardinski and Holme, 2011). Because at the observing point these effects comprise both the direct and the induced fields, and having in view the frequency difference of the SC variation in comparison to the secular variation, a suitable filter applied to data would eliminate both the external fields and their induced effects.…”
Section: Introductionmentioning
confidence: 99%
“…Working with annual means has the main advantage that short-lived ionospheric disturbances, primarily the Sq daily variation, can be neglected. Although the Sq signal does not cancel in an annual average, its amplitude stays below 2 nT at a typical mid latitude observatory as Niemegk according to a study spanning the years 1960-2001 by Verbanac et al (2007).…”
Section: Datamentioning
confidence: 99%
“…However, we note that consideration of only Dst does not provide the information of the geomagnetic activity at mid and high latitudes. Moreover, the observed Dst has contributions not only from the ring current, but also from magnetopause currents, tail currents, induced currents in the solid Earth, and other sources not yet fully quantified (e.g., Gonzalez et al 1994;Verbanac et al 2007). Verbanac et al (2011a and b), hereafter Paper I and Paper II, studied the geoeffectiveness of HSS/CIRs during the declining phase of the solar cycle 23, by employing various geomagnetic indices.…”
Section: Introductionmentioning
confidence: 99%